A particle-based numerical method for modelling of fluid-structure interactions in biomanufacturing processes - Lee, Jia Min (Nanyang Technological University, 2023)
The study of human physiology and target medicine has made a great leap with the discovery of cell culture, an operation under the more general topic of biomanufacturing. One key biomanufacturing technique for the creation of in-vitro three-dimensional tissue models and even diseases is the extrusion-based bioprinting, but the associated mechanical stresses can become so high that the cell viability significantly decreases. Therefore, methods that can characterize stresses induced in cell-laden bioinks during the printing process are critical to the advancement of bioprinting, ensuring high efficacy in the biomanufacturing technique. In this dissertation, a particle-based numerical method, commonly known as smoothed particle hydrodynamics (SPH), is developed to emulate the fluid-structure interactions between bioink and cells. To represent the cell deformations and motions, the SPH solver is coupled with an element bending group (EBG) model, which treats the cell as a solid membrane with liquid filling. The method is validated through comparison with experimental data on deformations and transport of a MCF7 cancerous cell through a microchannel. Upon validation, the method was applied on a model extrusion-based bioprinting configuration, considering in addition the use of cytoprotective gel particles to encapsulate the cells in the bioink, thereby maintaining a high cell viability. Using the deformations of the gel particles as boundary conditions, flow-induced stresses on the protective encapsulation can be computed by a separate finite element analysis. Stress analysis suggests the presence of a high stress region near the converging section before the bioprinter nozzle outlet, which is the likely cause of low cell viability in extrusion-based bioprinting. The results also indicate that the protective property from the encapsulating gel particles is due to the substitution of flow-induced stresses with internal stresses on the cells, which can be up to 90% less than the former. The findings from this research demonstrate that the two-dimensional SPH-EBG methodology developed here is a promising tool to predict stresses on cells within bioinks. Such a capability will not only facilitate the design of extrusion-based bioprinters, but also be applicable to other biomanufacturing techniques that involve cell-laden flows.